Deposit Insurance System in Poland and Its Place in Financial Safety Net - Ostalecka, Agnieszka (System gwarantowania depozytów w Polsce i jego rola w sieci bezpieczeństwa finansowego, 2010)
The aim of the article is to present the organization of deposit insurance system in Poland. As a starting point there are presented theoretical aspects of deposit insurance system functioning and its place in financial safety net. Against this background there are discussed detailed issues and assumptions of Bank Guarantee Fund functioning, like its main tasks, its powers, participants, categories of deposits included and excluded, guarantee limits and cooperation with other elements of financial safety net.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 103-113
Keywords: financial stability; financial safety net; deposit insurance; Bank Guarantee Fund